2016
DOI: 10.4103/2152-7806.176134
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus: Is there a place for brain stimulation?

Abstract: Tinnitus is the perception of a “phantom sound” and has a high prevalence. Although many therapies have been investigated within the last decades, there is still no effective standard therapy. Animal studies and human functional imaging studies revealed that tinnitus perception is associated with many complex changes in multiple brain structures. There is growing evidence that brain stimulation might be able to interrupt the local altered neuronal activity and hereby inhibit tinnitus perception. In this editor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…Interestingly, in Parkinson’s disease, a positive effect can also be obtained when different targets within the cortico-basal ganglia thalamic loop are stimulated ( Chiken & Nambu, 2014 ; Vitek, 2002 ). It can be postulated that tinnitus is also a network disorder, and disrupting the pathological information flow within the auditory network at any structure may suppress tinnitus ( van Zwieten et al., 2016 ). The exact mechanisms underlying the effects of high-frequency brain stimulation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in Parkinson’s disease, a positive effect can also be obtained when different targets within the cortico-basal ganglia thalamic loop are stimulated ( Chiken & Nambu, 2014 ; Vitek, 2002 ). It can be postulated that tinnitus is also a network disorder, and disrupting the pathological information flow within the auditory network at any structure may suppress tinnitus ( van Zwieten et al., 2016 ). The exact mechanisms underlying the effects of high-frequency brain stimulation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Despite decades of efforts to develop an effective therapy, it is still highly challenging to treat tinnitus. Multiple preclinical and clinical studies suggested deep brain stimulation (DBS) as a promising treatment option in severe, refractory tinnitus ( Smit et al., 2016 ; van Zwieten et al., 2018 ; van Zwieten, Smit, Jahanshahi, Temel, & Stokroos, 2016 ). Furthermore, electrical stimulation of the DCN with an auditory brainstem implant (ABI), which is used to elicit auditory sensations, can alter tinnitus loudness.…”
Section: Introductionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) has been proposed as a promising treatment option in severe, refractory tinnitus (21,22). Several reports on the effect of DBS in tinnitus have already been reported in humans (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) is a potential method of exerting a modulatory influence on auditory SG in tinnitus. DBS has recently emerged as a promising treatment option for tinnitus [15][16][17]. High-frequency stimulation (HFS) applied to the auditory pathway has been shown to effectively reduce tinnitus-like behavior in rats [18][19][20].…”
Section: Introductionmentioning
confidence: 99%